Heme Polymerization Inhibitory Activities of Xanthone from G. parvifolia (Miq) Miq Stem Bark as an Antimalarial Agent - Syamsudin; Supergiyono; Wahyuono, Subagus; Simanjuntak, Partomuan; Mustofa (Asian Journal of Chemistry, 2012)
A study had been conducted to isolate, to identify and to test heme polymerization inhibitory activities of G. parvifolia (Miq)Miq stem bark active compounds with antimalarial properties. UV, IR, RMI 1D (1H NMR and 13C NMR) and RMI 2D (COSY, HMQC and HMBC) and mass spectra were used for identification. Heme polymerization inhibitory activity assay was conducted in vitro by measuring b-hematin formation using ELISA reader. The study revealed that the active isolates derived from xanthone compounds, 1,3,6-trihydroxy-2-(3-methylbut-2-enyl)-7-methoxy-8-(3-methylbut-2-enyl)xanthen-9-on. HPIA assay showed that the compounds acted by inhibiting weak heme polymerization activities.